"No olho da rua": o serviço de atendimento social de rua em Porto Alegre - abordagem social de rua na sociedade contemporânea - Pizzato, Rejane Margarete Scherolt (2012)
The present study intended to examine the process of social street approach built in Porto Alegre through the Serviço Social de Rua ASR (Social Street Service) in Fundação de Assistência Social e Cidadania FASC. The choice of the theme of social street approach comes from the experience of the researcher, as a social worker, member of a multidisciplinary team that developed the Social Street Service over 14 years, in all areas of the city. The daily challenges marked by constant tensions understood in the mediation process of this social practice raised the motivation to perform this study. Its goal was based on analyzing the journey of the Serviço de Atendimento Social (Social Service Street Center), in order to provide insight and visibility of the social approach in ensuring the rights of the homeless population. This segment of the population, traditionally invisible to statistics, is for the first time recognized as a user of the Política Nacional de Assistência Social (National Social Policy), adopted in 2004 and brought to fruition only through the Sistema Único de Assistência Social SUAS (Social Welfare System). This system regulates and organizes the nationwide social welfare services from a decentralized and participatory model of management. Thus, it includes the social street approach service, in a decentralized way, in Centros de Referências Especializados da Assistência Social (Specialized Reference Centers of Social Welfare). This study, qualitative in nature, had as an issue understanding how the different individuals involved in the process of social street approach design and evaluate the ASR, developed in the 2000 to 2010 period, in Porto Alegre. As criteria for the inclusion, individuals who followed the service in the years 2000/2005/2010 were chosen, considered significant for the Service. Semi-structured interviews with 14 individuals were conducted: three managers, three users, three technicians, three monitors and two requesting the service. The interviews were recorded after the consent of the interviewees, transcribed and submitted to the process of content analysis according to Bardin (2010). The study was based on the dialectical historical materialism method. The survey results point to a context full of contradictions, tensions and clashes in the effectiveness of the social street approach. The homeless population is still very stigmatized and discriminated even by workers in social assistance policy. The methodology developed by ASR was a process built on the intervention on streets guided by the host, listening and formation of links with the homeless population. Another result of the survey indicated that the service of social street approach needs to be understood as part of a public state policy in which the worker is a public officer, representative of the state and not of a particular government. The user population still sees the social assistance as an aid and has little or no information about the PNAS and the SUAS. The increase of the homeless population in Porto Alegre did not lead to a significant increase of the ASR team. There was a gradual process of deterioration of the working conditions that resulted in a decrease in available treatment and increase of the daily restrained demand. The decentralization of the social street approach at CREAS represents a step forward in serving the homeless, but without the intersectionality, social welfare will remain responsible for the poverty of the city.